Gamified Simulation in Teaching and Learning Chemical Reaction for Grade 11 Senior High School - REGIL, ROSCELA MAE ARIZO (International Journal of Arts, Sciences and Education, 2026)
This study explored how online gamified simulation activities can enhance students’ learning of chemical reactions in Physical Science. Before the intervention, students showed limited understanding and struggled with key competencies such as identifying limiting reactants, distinguishing between limiting and excess reactants, and calculating product amounts. After engaging with the simulations, their performance improved noticeably, with the strongest gains in conceptual understanding. While computational skills also advanced, the progress was more modest. Student feedback reflected positive experiences, highlighting feelings of autonomy, competence, engagement, and appreciation for the functionality of the activities. Overall, the gamified simulations helped reduce misconceptions and strengthened conceptual grasp, though many learners still fell short of the expected proficiency benchmark. These findings suggest that gamified simulations are a powerful complement to traditional instruction, particularly for building deeper conceptual understanding, but they should be paired with scaffolded practice and guided problem-solving to fully support mastery of more complex quantitative tasks.